Comparative study in the net barter terms of trade and income terms of trade of the Pacific Island economies : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Economics at Massey University - Soakai, Robert Matafonua Fotu (Massey University, 1995)
It is suggested by the so-called P-S thesis that countries whose exports based upon traditional primary products will continue to face deterioration in their terms of trade. It is upon such a proclamation, that challenge the author to launched an investigation to the validity of such a claim and its applicability to the case of Solomon Islands, Tonga and Western Samoa. The early researcher in this area shows that countries whose exports dominate by exporting traditional primary commodities tend to have more instability in its terms of trade than those who are exporting manufactured goods. However one of the most staggering finding of this research is. The terms trade of the three island economies seem to be deteriorate, at same time their purchasing power seems to be on the positive side. What it means that, despite the deterioration in the country's terms of trade their incomes seem not deter at all by such a movement. This is sound controversial to the P-S thesis but there was other trade incentive that came in to play when these countries' terms of trade deteriorate. However, perhaps it is enough to mention here that such deterioration in the terms of trade might mean so little when one take into account major factors that hammered these small island's economies. Factors like, drought, hurricane, poor quarantine service, has fueled the problem of deterioration of the terms of trade. Empirical test was carried out to examine the impact of the Net Barter terms of trade movement on the income (Gross Domestic Products). Result revealed was un-intrigue. Conclusion was drawn and there is a strong need for change in the export haves of the three island economies. Policies need to change to encourage regional trading. A change to the trade agreement (e.g., SPARTECA) that govern the trade activities of the island nations, is necessary. Such a change will help the island nations to compete with its trading partners effectively and competatively.
Keywords: Solomon Islands; Samoa; Tonga; Oceania; Terms of trade